Application of the Relative Citation Ratio to Assess Common Characteristics of the Highest Impact Articles in Reconstructive Microsurgery - Amir-Ala Mahmoud; Dominick J. Falcon; Valeria P. Bustos; Maria J. Escobar-Domingo; Bernard T. Lee (Archives of Plastic Surgery)
Background The purpose of this review is to characterize themes among the five reconstructive microsurgery articles achieving the highest Relative Citation Ratios (RCRs) published in the past 20 years in the top journals. In doing so, researchers may be better informed on how to propose salient research questions to impact the field and understand future directions in plastic surgery.